Development of Superior Character through the Role of Family, School, and Community in Quality Character Formation - Yelpia Septi Mayenti; Elly Malihah (JURUSAN MANAJEMEN PENDIDIKAN FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI GORONTALO, 2023)
Character education plays a crucial role in restoring national identity and fostering the development of a new Indonesian society. This research employed a literature review approach, drawing data from articles published in Sinta and Scopus indexed journals. The content analysis method was used to analyze the collected data. The findings indicate that nurturing students' character is a complex and gradual process that demands continuous effort and thoughtful reflection. Ethical decisions made during this process must be translated into practical actions, enabling individuals to become practical and wise in their conduct. Transforming these actions into habits and shaping one's character or disposition takes considerable time. Character education necessitates the involvement of multiple stakeholders, including families, schools, and communities. Reconnecting the educational networks and relationships among these three environments is the first crucial step. The successful formation of educational values and character traits relies on the harmonious and continuous interaction between these three contexts. Recognizing this reality, it becomes evident that a holistic development of student personality requires a strong influence from family, school, and society